THE INFLUENCE OF TEACHER WORKING GROUP PERFORMANCE AND SCHOOL PRINCIPAL'S ROUTINE SUPERVISION ON SCHOOL QUALITY - Nurjamilah (Institut Pendidikan Indonesia, 2021)
This research aims to analyze the influence of the implementation of KKG and routine supervision of school principals on improving the quality of elementary schools, especially in Garut Kota District. The method used in this research is a correlational descriptive method. The object of research and also the population in this research are school principals and elementary school teachers in Garut Kota District. Meanwhile, 137 respondents were sampled in this study, drawn equally from school principals and teachers. The data collection techniques used were documentation studies and field studies. Meanwhile, the data analysis technique used to answer the hypothesis is statistical analysis using a path analysis model. The results of research on the implementation of the KKG in Garut Kota District are felt by teachers to be not optimal, so efforts need to be made to further improve various activities that are beneficial for the development of teacher professionalism. Routine supervision of school principals shows that in general elementary school principals in Garut Kota District have not fully carried out routine supervision as they should. The quality of the school also shows quite good criteria. The results of research hypothesis testing can be concluded that the implementation of KKG and routine supervision of school principals has a positive influence on improving the quality of elementary schools in Garut City District, Garut Regency, both individually and jointly (simultaneously).